The fiesta as a key concept of Spanish linguistic culture - E. V. Astakhova (Ибероамериканские тетради, 2015)
The author examines the image of Spain through the megaconcept of fiesta, which determines many aspects of the national and cultural mentality. This concept reflects various vectors of quotidian life, religious and popular holidays with their complicated details and special dramaturgy, penetrates to every day communication and behavior. The research determines such Spanish extralinguistic realities as corrida, tertulia, movida, botellon, indignados, analyses the role of the theater, of “coffee culture”, of football and other phenomenons in social life and cognitive space of Spaniards. The knowledge of different aspects of fiesta helps to understand the word potential of Spanish language, its metafores, stylistic images.